INFLUENCE OF STABILIZATION EXERCISES ON ARTICULAR CARTILAGE CHANGES IN DEGENERATIVE TIBIO- FEMORAL JOINT DISEASE- A PILOT STUDY - Apparao, Patchava; S, Sudhakar; Ch, Ganapathi Swamy; Reddy, Ravi Shankar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: To determine the effectiveness of knee joint stabilization exercises in minimizing articular cartilage degeneration and to examine the effectiveness of knee joint stabilization exercises on decreasing pain, improving range of motion (ROM) and muscle strength. Methods: About 20 volunteer subjects (age 35-65 years) with primary osteoarthritis fulfilled the inclusion criteria given the knee stabilization exercises for 8 weeks. Pain, muscle strength, functional outcome score, and serum cartilage oligomeric matrix protein (COMP) values were measured pre- and post-intervention using visual analog scale, dynamometer, and ELISA test. Data were analyzed using a paired t-test with Statistical Package for the Social Sciences version 20 to find out the difference between the pre- and post-test. Results: The results of the study have shown that significant difference between pre- and post-test values of pain, ROM, muscle strength and functional outcome score with p<0.05, and there is statistical in significance in serum COMP value (p<0.05). Conclusion: Stabilization exercises of knee joint were shown to be beneficial for decreasing pain, improving ROM and muscle strength, and there was no effect on articular cartilage changes in degenerative tibiofemoral joint disease. Keywords: Serum cartilage oligomeric matrix protein, Knee stabilization exercises, Proprioception exercises, Muscle strength. Â Â 